Physiological tipping points in the relationship between foraging success and lifetime fitness of a long‐lived mammal - Roxanne S. Beltran; Keith M. Hernandez; Richard Condit; Patrick W. Robinson; Daniel E. Crocker; Chandra Goetsch; A. Marm Kilpatrick; Daniel P. Costa (Ecology Letters, 2023)
Although anthropogenic change is often gradual, the impacts on animal populations may be precipitous if physiological processes create tipping points between energy gain, reproduction or survival. We use 25 years of behavioural, diet and demographic data from elephant seals to characterise their relationships with lifetime fitness. Survival and reproduction increased with mass gain during long foraging trips preceding the pupping seasons, and there was a threshold where individuals that gained an additional 4.8% of their body mass (26 kg, from 206 to 232 kg) increased lifetime reproductive success three‐fold (from 1.8 to 4.9 pups). This was due to a two‐fold increase in pupping probability (30% to 76%) and a 7% increase in reproductive lifespan (6.0 to 6.4 years). The sharp threshold between mass gain and reproduction may explain reproductive failure observed in many species and demonstrates how small, gradual reductions in prey from anthropogenic disturbance could have profound implications for animal populations.

Energy-Rich Mesopelagic Fishes Revealed as a Critical Prey Resource for a Deep-Diving Predator Using Quantitative Fatty Acid Signature Analysis - Chandra Goetsch; Melinda G. Conners; Suzanne M. Budge; Yoko Mitani; William A. Walker; Jeffrey F. Bromaghin; Samantha E. Simmons; Colleen Reichmuth; Daniel P. Costa (Frontiers in Marine Science, 2018)

Fisheries Exploitation by Albatross Quantified With Lipid Analysis - Melinda G. Conners; Chandra Goetsch; Suzanne M. Budge; William A. Walker; Yoko Mitani; Daniel P. Costa; Scott A. Shaffer (Frontiers in Marine Science, 2018)